Near fatal desquamative interstitial pneumonia with bilateral recurrent tension pneumothorax - Park, Dong Won; Kim, Tae Hyung; Shon, Jang Won; Yoon, Ho Joo; Park, Sung Soo; Jeon, Seok Chol; Choi, Yo Won; Paik, Seung Sam; Kim, Hyuck (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Desquamative interstitial pneumonia (DIP) is an uncommon form of interstitial lung disease demonstrating good response to corticosteroid therapy and favorable prognosis. In rare cases, patients with DIP fail to respond to corticosteroid therapy, and may progress to end-stage fibrotic lung disease with respiratory failure. For such patients, well defined treatment regimen does not exist until now. We report a rare case of near fatal DIP with recurrent bilateral tension pneumothorax despite of corticosteroid maintenance therapy. Clinical and radiological findings improved with surgical intervention in addition to combination therapy with prednisolone and clarithromycin. The patient has remained in an improved state and has been receiving prednisolone and clarithromycin for 9 months. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 167-171)